2012
DOI: 10.1084/jem.20111493
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of SLP-76 and ADAP for neutrophil recruitment in mouse kidney ischemia-reperfusion injury

Abstract: Leukocyte recruitment to the kidney during acute injury is mediated by E-selectin–mediated rolling and requires SLP-76 and the adaptor protein ADAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
115
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 73 publications
0
115
2
1
Order By: Relevance
“…This step is defective in mice lacking either the Src kinase Fgr or both Hck and Lyn (19): neutrophils from these mice fail to consecutively phosphorylate the spleen tyrosine kinase (Syk) (19). Syk activates a protein complex of the Src homology 2 domaincontaining leukocyte phosphoprotein of 76 kDa (SLP76) and the adhesion and degranulation-promoting adaptor protein (ADAP) (20). SLP76, in turn, activates Bruton tyrosine kinase (20).…”
Section: Leukocyte Recruitmentmentioning
confidence: 99%
See 3 more Smart Citations
“…This step is defective in mice lacking either the Src kinase Fgr or both Hck and Lyn (19): neutrophils from these mice fail to consecutively phosphorylate the spleen tyrosine kinase (Syk) (19). Syk activates a protein complex of the Src homology 2 domaincontaining leukocyte phosphoprotein of 76 kDa (SLP76) and the adhesion and degranulation-promoting adaptor protein (ADAP) (20). SLP76, in turn, activates Bruton tyrosine kinase (20).…”
Section: Leukocyte Recruitmentmentioning
confidence: 99%
“…Syk activates a protein complex of the Src homology 2 domaincontaining leukocyte phosphoprotein of 76 kDa (SLP76) and the adhesion and degranulation-promoting adaptor protein (ADAP) (20). SLP76, in turn, activates Bruton tyrosine kinase (20). Both Bruton tyrosine kinase and ADAP are needed to signal downstream via two independent branches (20): one is phospholipase C (PLC)g2 dependent and comprises Calcium diacylglycerol guanine nucleotide exchange factor I (CalDAG-GEFI), p38 MAPK, and Rap1a (21).…”
Section: Leukocyte Recruitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In platelets, loss of ADAP results in impaired a IIb b 3 integrin activation, leading to increased rebleeding of ADAPdeficient mice from tail wounds (20) and to instable thrombus formation after carotid artery injury in vivo (21). Recently, it was shown that loss of ADAP attenuated neutrophil recruitment in an ischemia-reperfusion-induced acute kidney injury model (22).…”
mentioning
confidence: 99%